Role of Myeloid-Epithelial-Reproductive Tyrosine Kinase and Macrophage Polarization in the Progression of Atherosclerotic Lesions Associated With Nonalcoholic Fatty Liver Disease - Pastore, Mirella; Grimaudo, Stefania; Pipitone, Rosaria Maria; Lori, Giulia; Raggi, Chiara; Petta, Salvatore; Marra, Fabio (Frontiers in Pharmacology, 2019)
Non-alcoholic fatty liver disease (NAFLD) is considered the hepatic manifestation of metabolic syndrome, being closely related to obesity, insulin resistance and oxidative stress. It includes a spectrum of conditions ranging from simple steatosis, characterized by hepatic fat accumulation with or without inflammation, to non-alcoholic steatohepatitis (NASH), defined by hepatic fat deposition with hepatocellular damage, inflammation and accumulating fibrosis. Several studies support an association between NAFLD and the incidence of cardiovascular diseases including atherosclerosis, a major cause of death worldwide. This pathological condition consists in a chronic and progressive inflammatory process in the intimal layer of large and medium sized arteries. The complications of advanced atherosclerosis include chronic or acute ischemic damage in the tissue perfused by the affected artery, leading to cellular death. In an atherosclerotic plaque, phagocytosis of apoptotic cells occurs through efferocytosis, a physiological process essential in maintaining immune homeostasis. A defective efferocytosis is able to induce post-apoptotic necrosis during maturation of atherosclerotic lesions. Although a diversity of phagocyte subpopulations is involved in atherosclerosis, a particular subset of macrophages (anti-inflammatory M2 phenotype) is spatially linked to necrotic core. The activation state of macrophages depends on their metabolic state, indeed in acutely inflamed hypoxic tissues, anaerobic glycolysis promotes a program of macrophage M1 polarization, whereas aerobic metabolism favors M2 activation. Lipid metabolism is associated with immune regulatory macrophage responses, modulating towards a pro-inflammatory M1 phenotype or an anti-inflammatory M2 phenotype controlled by several transcription factors. Recent lines of evidence highlighted the involvement of Myeloid-epithelial-reproductive Tyrosine Kinase (MerTK) in metabolic disease associated with liver damage. MerTK is mainly expressed in M2c macrophages and is involved in efferocytosis, mediates transcriptional changes, including suppression of proinflammatory cytokines and enhancement of inflammatory repressors. This review highlights the impact of MerTK in macrophage alternative activation and its possible role in NAFLD-associated atherosclerotic lesions as a potential therapeutic target.